ANALISIS NILAI DENSITAS DAN NET CALORIFIC VALUE SERTA KEBERADAAN AIR LINDI PASAR TRADISIONAL (STUDI KASUS DI PROVINSI SULAWESI UTARA) - Vinny Virginia Moningka; Zetty E. Tamod; Wenny ., Tilaar (Sam Ratulangi University, 2021)
This study aims to analyze the density and net calorific value and analyze the traditional market waste leachate. The sampling locations were in traditional markets in 5 districts/cities, namely Manado City, Bitung City, North Minahasa Regency, Minahasa Regency, and Tomohon City. This research was conducted in May – August 2021. The method used in this study is a quantitative descriptive survey research method and tabulated analysis equipped with a histogram graph. Visiting and observing at the research site then combining it with primary and secondary data. Primary data in the form of waste samples to be observed and secondary data in the form of information or supporting documents from related parties. The parameters observed were the density of traditional market waste, calculating the Net Calorific Value of each waste sample, and analysis of pH, TDS, TSS, EC in traditional market waste leachate. The conclusion of this study is that organic waste shows the highest density value in 5 regencies/cities and the average net calorific value of 5 regencies/cities ranges from 7000 kcal/kg – 8000 kcal/kg and the presence of leachate in traditional market waste shows high TDS value. Likewise, the EC value indicates the presence of cation ions in the leachate. The presence of leachate is intended not as a pollutant component but as an indicator that can provide nutrients for plant growth.